Peningkatan Kapasitas Aws Untuk Lingkungan Outdoor - Fajrin, Alvin Nur; Dewanta, Favian; Nuha, Hilal Hudan (eProceedings of Engineering, 2024)
The website on the weather station is a system that integrates weather station devices into media information. Users can control and monitor weather station device parameters in real-time through the website. The integration of these two systems is known as the Internet of Things (IoT). This research creates a website that can perform control, such as changing the operating mode for weather station devices to regulate sensor working intervals. The creation of control modes for weather stations is done by configuring media information to weather station devices. This configuration still requires improvement to enhance the user experience. The control mode system is added to the monitoring page, making it easier for users to monitor and control weather station devices on the same page. Keywords: IoT, Website, Controlling, Operation Mode